Recurrent Hepatitis C Post-Transplantation: Where Are We Now and Where Do We Go From Here? A Report from the Canadian Transplant Hepatology Workshop. (2006) - Watt, Kymberly DS; Burak, Kelly; Deschênes, Marc; Lilly, Les; Marleau, Denis; Marotta, Paul; Mason, Andrew; Peltekian, Kevork M; Renner, Eberhard L; Yoshida, Eric M; ,
Abstract : Approximately 400 liver transplants are performed in Canada every year and close to 6000 per year in the United States. Forty per cent to 45% of all liver transplants are performed for patients with underlying hepatitis C virus (HCV)-related liver disease. These patients have a different natural history, new complication risks and different treatment efficacy than nontransplant HCV patients. Every effort must be made to identify those patients at highest risk for progressive liver disease post-transplant. Recurrent HCV is an Achilles' heel to transplant hepatology. The true natural history of this disease is only starting to unravel and many questions remain unanswered on the optimal management of these patients after liver transplantation. The present report summarizes the literature and ongoing research needs that are specific to HCV-related liver transplantation.